2008
DOI: 10.1007/s11250-008-9218-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doe milking and supplementation using Dichrostachys cinerea pods on kid and doe performance in grazing goats during the dry season

Abstract: Effects of supplementation and milking of Matebele does four weeks pre-partum to weaning, on milk yield, kid birth weight and growth rate were studied. Forty does were divided into four treatments: supplemented and milked (SM), supplemented and not milked (SNM), not supplemented and milked (NSM); and not supplemented and not milked (NSNM). Supplemented goats were given 200 g/doe/day of Dichrostachys cinerea pods containing 19% CP. The study was carried out in September during time of feed unavailability and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
6
1
Order By: Relevance
“…The average kid birth weight (2.04 kg) recorded in this study is lower compared to reports from other parts of Africa (Aganga et al, 2005;Maphosa et al, 2009). This higher birth weight in other studies may be due to breed difference including difference in twining and tripleting.…”
Section: Factors Affecting Kid Birth Weightcontrasting
confidence: 85%
“…The average kid birth weight (2.04 kg) recorded in this study is lower compared to reports from other parts of Africa (Aganga et al, 2005;Maphosa et al, 2009). This higher birth weight in other studies may be due to breed difference including difference in twining and tripleting.…”
Section: Factors Affecting Kid Birth Weightcontrasting
confidence: 85%
“…Goats possess the potential to produce milk for rural households when cow milk is limited [3]. In addition, most communal goat farmers may not be able to afford to keep exotic goat breeds for the purpose of milk production because of financial constraints and the expertise to manage them in communal areas [4]. Exotic dairy goat breeds are more expensive and are often susceptible to disease and parasite infestation than indigenous goat breeds that are well-adapted to harsh environmental conditions and are less expensive to maintain [5].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be borne in mind that pod supplements are available locally and pose no special storage requirements for small-scale farmers in remote rural areas. In another study, although doe weights of Matabele goats grazing on natural pasture were similar (P >0.05) to those that were supplemented with D. cinerea, kid weaning weights were higher (P <0.05) in those supplemented with D. cinerea compared with the unsupplemented group (Mlambo et al, 2004;Maphosa et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Woody plant pods, especially those from Vachellia species and D. cinerea, are valuable because they ripen and drop off well into the dry season (Timberlake et al, 1999). Pods are a good source of crude protein (100-190 g/kg dry matter (DM)) and have been reported to increase the growth of kids and of milk production in goats (Mlambo et al, 2004;Maphosa et al, 2009). Mlambo et al (2004) reported a 60% reduction in urinary nitrogen excretion in goats that was offered untreated D. cinerea fruits.…”
Section: Introductionmentioning
confidence: 99%